Mixed Methods Research Design Concepts: Quantitative, Qualitative, Exploratory Sequential, Exploratory Sequential, Embedded and Parallel Convergent - Candra Susanto, Primadi; Ulfah Arini, Dewi; Marlita, Devi; Yuntina, Lily; Saribanon, Euis (International Journal of Advanced Multidisciplinary, 2024)
The purpose of this literature research is to help future authors determine the right research design. Research article Mixed Methods Research Design Concepts: Quantitative, Qualitative, Exploratory Sequential, Exploratory Sequential, Embedded, and Parallel Convergent is a scientific literature article within the scope of research methodology. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous studies that are relevant to this research and are sourced from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Quantitative is related to the Concept of Mixed Methods Research Design; 2) Qualitative is related to the Concept of Mixed Methods Research Design; 3) Sequential Exploratory is related to the Concept of Mixed Methods Research Design; 4) Exploratory Sequential relates to the Mixed Methods Research Design Concept; 5) Embedded relates to the Mixed Methods Research Design Concept; and 6) Parallel Convergent relates to the Mixed Methods Research Design Concept.